Green-solvent-soluble, highly efficient dopant-free hole-transporting material for perovskite solar cells. (1st January 2023) - Onozawa-Komatsuzaki, Nobuko; Tsuchiya, Daisuke; Inoue, Shinichi; Kogo, Atsushi; Ueno, Toshiya; Murakami, Takurou N.
Abstract: Halogenated solvents (e.g. chlorobenzene and chloroform) are typically used for hole-transporting materials (HTMs) in perovskite solar cells (PSCs); however, their use should be avoided as they are known to be hazardous to the environment. Herein, we synthesized a nonhalogenated-solvent-soluble, dopant-free HTM, SF62 . When depositing HTMs for PSCs, SF62 could be dissolved with a nonhalogenated and green solvent, ethyl acetate. It is one of the most common organic solvents and is known to have a low environmental impact. Non-doped-SF62 -based PSCs exhibited higher power-conversion efficiency (18.6%) than doped 2, 2′, 7, 7′-tetrakis( N, N -di-p-methoxyphenylamino)-9, 9′-spirobifluorene (Spiro-OMeTAD )-based ones (18.3%), with enhanced stability.